Pengembangan Konsep Lemari Multifungsi Minimalis Menggunakan Metode Quality Function Deployment - Irvan, Muhammad; Thaufani, Argi; Wibisono, Deny (BULLET : Jurnal Multidisiplin Ilmu, 2025)
The various types of daily necessities for general public and the activities related to these items, lead people to think about the need for multifunctional wardrobe. Currently, there are many different types of wardrobe models sold on the market, one wardrobe design that remains much sought after is the modern minimalist style. The ability of a company to identify, understand customer needs, and be able to create a product quickly, is a challenge for furniture companies to meet the need for multifunctional and minimalist wardrobe. This research aims to provide a solution for developing a multifunctional and minimalist wardrobe concept, which can be used by furniture companies in facing these challenges. The multifunctional and minimalist wardrobe design was developed using the Quality Function Deployment (QFD) method, by creating a House of Quality (HOQ) to determine the technical parameters that provide the greatest priority value in efforts to develop the right product concept. As a results, the technical parameters that are the focus of designing this minimalist multifunctional wardrobe product are related to consumer needs and desires for affordable prices and minimalist sizes, that is: 'concept design', 'additional functions', and minimalist 'product dimensions'. Based on the priority of these technical parameters, the abstraction of the proposed wardrobe concept idea is: 'A minimalist multifunctional wardrobe design using strong materials at an affordable price, and having lots of storage space'.